PENGUJIAN TECHNOLOGY ACCEPTANCE MODEL (TAM) ATAS APLIKASI INTERNAL SOFTWARE MY QUICK ACCOUNTING SYSTEM (MY QAS) - Jurica Lucyanda (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2007)
The purpose of this study is to examine the factors that determine intention of the accounting student to adopt internal software My Quick Accounting System (My QAS) in Economic Faculty of Islamic University “45” BekasL To identify the factors that affect intention to adopt internal software using a research model based on Technology Acceptance Model (TAM), The respondent in this study that only the accounting students who have participated in accounting computer course. This study using the survey method for data collection (personally administrated questionnaires). The results indicate that the accounting: student’s intention to adopt My QAS determine by factors: perceived usefulness, perceived ease of use.